Effects of education and age on the experience of youth violence in a very low-resource setting: a fixed-effects analysis in rural Burkina Faso - Kuunibe, Naasegnibe; Bountogo, Mamadou; Ouermi, Lucienne; Sié, Ali; Bärnighausen, Till; Harling, Guy (BMJ open, 2023)
Objective The study aimed to investigate the effects of education and age on the experience of youth violence in low-income and middle-income country settings. - Design Using a standardised questionnaire, our study collected two waves of longitudinal data on sociodemographics, health practices, health outcomes and risk factors. The panel fixed-effects ordinary least squares regression models were used for the analysis. - Settings The study was conducted in 59 villages and the town of Nouna with a population of about 100 000 individuals, 1 hospital and 13 primary health centres in Burkina Faso. - Participants We interviewed 1644 adolescents in 2017 and 1291 respondents in 2018 who participated in both rounds. - Outcome and exposure measures We examined the experience of physical attacks in the past 12 months and bullying in the past 30 days. Our exposures were completed years of age and educational attainment. - Results A substantial minority of respondents experienced violence in both waves (24.1% bullying and 12.2% physical attack), with males experiencing more violence. Bullying was positively associated with more education (β=0.12; 95% CI 0.02 to 0.22) and non-significantly with older age. Both effects were stronger in males than females, although the gender differences were not significant. Physical attacks fell with increasing age (β=−0.18; 95% CI −0.31 to -0.05) and this association was again stronger in males than females; education and physical attacks were not substantively associated. - Conclusions Bullying and physical attacks are common for rural adolescent Burkinabe. The age patterns found suggest that, particularly for males, there is a need to target violence prevention at younger ages and bullying prevention at slightly older ones, particularly for those remaining in school. Nevertheless, a fuller understanding of the mechanisms behind our findings is needed to design effective interventions to protect youth in low-income settings from violence.